Моделювання багатокомпонентного коливального руху вібраційної системи з лінійним електроприводом - Бондар, Р.П.; Голенков, Г.М.; Мазуренко, Л.І.; Подольцев, О.Д. (Технічна електродинаміка, 2012)
The Simulink-model of two-mass oscillatory vibrating system is developed and investigated. This system consist of the linear electric motor with permanent magnets. Resonant properties of the system and efficiency of power transfer is studied. Possibility of simultaneous use of two and three linear motors to produce of multicomponent movement of a vibrating platform is considered. It is shown that at various values of amplitudes, phases and frequencies of voltage sources of the motors of the complicated forms of the oscillatory can be obtained.